2020
DOI: 10.1200/jco.2020.38.15_suppl.9039
|View full text |Cite
|
Sign up to set email alerts
|

Real-world survey of pneumonitis/radiation pneumonitis among patients with locally advanced non-small cell lung cancer treated with chemoradiotherapy after durvalumab approval: A multicenter retrospective cohort study (HOPE-005/CRIMSON).

Abstract: 9039 Background: Durvalumab was approved as a consolidation therapy after chemoradiotherapy (CRT) for locally advanced non-small cell lung cancer (NSCLC) and established as the standard of care. However, since the approval of durvalumab, little has been reported on the frequency, severity, or clinical course of pneumonitis/radiation pneumonitis throughout the course of CRT. Methods: We conducted a 17-center, retrospective cohort study of consecutive patients with locally advanced NSCLC who received concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Suresh et al indicated that the rate of ICI-induced pneumonitis in lung cancer patients could be as high as 7–19% ( Suresh et al, 2018 ). A study reported a rate of 33% of pneumonitis with any symptoms (grade ≥2) ( Saito et al, 2020 ). A meta-analysis showed that the pooled rates of grades 2, 3, 4, and 5 pneumonitis were 17.8, 7.9, and 14%, respectively ( Dawe et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suresh et al indicated that the rate of ICI-induced pneumonitis in lung cancer patients could be as high as 7–19% ( Suresh et al, 2018 ). A study reported a rate of 33% of pneumonitis with any symptoms (grade ≥2) ( Saito et al, 2020 ). A meta-analysis showed that the pooled rates of grades 2, 3, 4, and 5 pneumonitis were 17.8, 7.9, and 14%, respectively ( Dawe et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…pneumonitis/RT-pneumonitis with the PACIFIC regimen [31]. Thyroid disorders, including hypothyroidism (8.8%) and hyperthyroidism (2.5%), were the most common non-pneumonitis imAEs in PACIFIC, with a total incidence of 11.4% among patients who received durvalumab.…”
Section: Tablementioning
confidence: 99%
“…In the PACIFIC trial, any grade pneumonitis occurred at a rate of 33.9% in patients receiving durvalumab, with grade ≥ 3 pneumonitis occurring in 3.4% (24.8 and 2.6% in the placebo arm, respectively) [10]. Real-world data have reported frequencies of any grade and grade ≥ 3 pneumonitis of 20-80% and approximately 6%, respectively, with some studies reporting pneumonitis as a negative prognostic factor for survival [18,57,59,60]. Pneumonitis is a particularly concerning immune-related adverse event in patients with stage III lung cancer, as prior radiotherapy may act synergistically to increase its risk of occurrence [61].…”
Section: Immunotherapy: Treatment Initiation and Managementmentioning
confidence: 99%
“…Re-challenge with durvalumab can be considered after resolution of symptoms; however, guidelines on safely re-challenging are limited [60]. In two small retrospective studies, re-challenge with durvalumab was shown to be feasible, leading to pneumonitis recurrence in 14 and 29% of patients [59,60]. To optimize patient outcomes, the decision of durvalumab re-challenge should be made with an MDT.…”
Section: Immunotherapy: Treatment Initiation and Managementmentioning
confidence: 99%